Towards integrated water resources management through modeling, optimization, and stakeholder engagement with a decision support game - Dozier, André, author; Arabi, Mazdak, advisor; Grigg, Neil, committee member; Pallickara, Shrideep, committee member; Pritchett, James, committee member (Colorado State University. Libraries, 2017)
Integrated water resources management (IWRM) necessitates stakeholder engagement and integrated assessment of physical, ecological, and socioeconomic systems. Water resource literature has reflected a trend toward IWRM through increased focus on model integration, evolutionary and multiobjective algorithms, and stakeholder engagement through participatory modeling and role-playing games. A model data passing interface exemplifies integrated assessment with minimally invasive and interoperable code changes. IWRM is applied within the context of a rapidly urbanizing, semi-arid region with steadily declining agricultural production and community welfare. Integrated modeling and assessment of the South Platte River Basin reveals lessons about management objectives, allocation institutions, and characterization of optimal solutions. High prices of water incentivize farmers to sell, while managing to sustain agriculture reduces price, saving money for cities. Freer trade can combat potential water supply vulnerabilities. Biased reservoir operations limit benefits from additional reservoir capacity. Optimized selection between a limited set of supply-side and demand-side solution strategies exposes the sensitivity of optimal outcomes to municipal raw water purchase requirements and the cost-effectiveness of xeriscaping and more efficient agricultural irrigation technology. A promising and novel, yet preliminary and proof-of-concept, decision support game is demonstrated to reconcile numerical simulation and optimization techniques with stakeholder engagement and preference-based alternative selection.
Keywords: games with a purpose; model integration; water; hydrology; drought; multiobjective optimization